Novel Coronavirus (COVID-19) Pandemic: The Role of Printing Media in Asian Countries - Parvin, Gulsan Ara; Ahsan, Reazul; Rahman, Md. Habibur; Abedin, Md. Anwarul (Frontiers in Communication, 2020)
Media frames our understanding and creating powerful forces at the individual and societal level during all critical incidents. Media also can negatively affect the mental health of its readers after any tragic events. So it can be said that media has a proactive role in shaping the mass population’s actions and thereby influences policy actions. Especially, printing media considered a key factor in taking the information to the mass. However, in this ICT era, people are reluctant to carry hard copies of newspapers rather than fond of e-newspapers. In present days, whole papers, especially opinions sections, are overwhelmed with the concerns of the pandemic caused by Novel Coronavirus, named COVID-19. After China and Japan, different countries in Asia started their fights against the COVID-19 outbreak at a different time from January to March. All affected countries came forward to manage the pandemic in their way following lessons learned from China and Japan. Media in every form of affected countries highlight their concern to present news, perceptions, and opinions related to the coronavirus outbreak. Since opinions or editorials are the key section of e-newspapers that reflect experts’ perceptions and thoughts, this study aims to examine the experts’ views of e-newspapers of five different countries in Asia, concerning China and Japan. Considering the diversity in socio-economic and geopolitical settings, five states viz. South Korea, Singapore, Iran, India, and Bangladesh, having one leading English e-newspaper of each country, are selected. This paper explores how experts’ perceptions in studied countries present different aspects of life. Also, which newspaper has emphasized which aspect of life and in which period of the outbreak. By intensive text mining in each selected e-newspaper, it found that diversified issues regarding COVID-19 were addressed by the experts’ opinions. These different issues grouped into eight aspects that are Health and Drug, Preparedness, Social welfare and Humanity, Economy, Governance, Politics, Environment and Wildlife, Innovation, and Technology. This study pioneers to present a similar picture of experts’ concerns in five different newspapers in Asian countries from January to March in shaping health crises and thus contributing to policy actions.